(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Can quantum information systems be understood using local realism? The consensus is No. Quantum information is based on qubits and Bell states. According to conventional wisdom these cannot be understood using local realism. Invariably local realism is assumed, incorrectly, to refer only to the Einstein, Podolsky and Rosen (EPR) model. Today a radically different model of local realism has arisen. The Theory of Elementary Waves (TEW) is incompatible with Einsteins picture of reality but nevertheless is local and realistic. We show that the Bell test experiments that invalidate EPR, validate TEW! This article uses TEW to reproduce all four Bell states. From TEW we derive the Bell states. We also show that TEW can explain an experiment using remote entangled photons that have no shared history, which are entangled because ofentanglement swapping. The implications of our study for quantum information theory are unclear, except that the term nonlocal should be replaced with a more precise and fruitful term. Nonlocal is vague and misleading. Elementary ray is a verifiable and precisely defined term that can replace it. This paradigm shift could inspire a new generation of quantum information experiments.